ChemInform Abstract: Low‐Temperature Gasification of Biomass and Lignite: Consideration of Key Thermochemical Phenomena, Rearrangement of Reactions, and Reactor Configuration. Issue 11 (18th March 2014) - Hayashi, Jun‐ichiro; Kudo, Shinji; Kim, Hyun‐Seok; Norinaga, Koyo; Matsuoka, Koichi; Hosokai, Sou
Abstract Review: 179 refs.